Mediating Role of Tabṣirah in Fashion Purchase Decisions Among Middle-Class Women - Silfadilla Syaputri; Syaparuddin Razak; Munawarah (Scimadly Publishing, 2026)
This study examines the mediating role of tabṣirah in fashion purchase decisions among middle-class Muslim women. Grounded in the Engel–Blackwell–Miniard (EBM) Consumer Decision Model and mediation theory, the study investigates how consumer motivation, information search, and attitudes toward fashion products influence purchase decisions through tabṣirah as an ethical–spiritual mechanism. A quantitative explanatory approach was employed using survey data collected from 151 Muslim women in Bone Regency, South Sulawesi, Indonesia. The data were analyzed using PLS-SEM. The results reveal that consumer motivation, information search, and attitudes toward fashion products significantly influence tabṣirah. Tabṣirah has a strong positive effect on fashion purchase decisions. The mediation analysis confirms that tabṣirah fully mediates the relationships between consumer motivation, information search, attitudes toward fashion products, and fashion purchase decisions. These findings indicate that psychological and cognitive factors influence purchasing behavior only after being transformed into reflective moral awareness and Sharia-compliant judgment. The study contributes to Islamic consumer behavior literature by extending the EBM model through the integration of tabṣirah as an ethical–spiritual mediating construct and provides practical implications for promoting responsible and value-based fashion consumption among Muslim consumers.